Roles of Adult Education Programmes in Poverty Alleviation in Okrika and Port Harcourt City Local Government Area, Rivers State (Global Journal of Human-Social Science, 2020)
This study examined the roles of adult education programmes in poverty alleviation in Okrika and Port Harcourt City Local Government Areas of Rivers State. 3 research questions and 3 research objectives guided the study. 3 hypotheses were also tested at 0.05 significant level. The study adopted analytical survey design with a population of 5653 beneficiaries of Rivers State Government adult education programmes for Poverty Alleviation in the area of study, out of which 2,828 beneficiaries were proportionately sampled. The instrument used for data collection was a validated researcher-made questionnaire titled "Roles of Adult Education Programmes in Poverty Alleviation Questionnaire". The instrument has a reliability index of 0.74. Data obtained were analysed with percentages, mean statistic and T-Test. Findings of the study revealed that adult education programmes designed for poverty alleviation in Okrika and Portharcourt Local Government Areas are, functional literacy, vocational skills and technical education. That these adult education programmes have promoted capacity building, improve productivity; and requisite vocational /occupational skills for self-reliance among community members.
Keywords: adult education; adult education programmes; poverty; poverty alleviation